Speech Competence Testing and Assessment: German Approach - Tarasiuk, Inna (East European Journal of Psycholinguistics, 2019)
Methods and approaches of foreign language teaching being changed considerably of late, the assessment of the language competence should be consistent with clear international standardization requirements. Since the article has a brief informative character, the notion of evaluation as an inducement to a corresponding speech reaction or action through the well-defined communicative tasks is defined. Such types of evaluation as formal and informal, external evaluation and a self-assessment are outlined in the article. Different functions of speech competence assessment were covered, as it is important to understand its purpose. Among them  are diagnostics, encouragement, progress recognition, the statement of goals achievement, the setting of rating, grading, comparison, motivation. Since there are two subjective pictures of the objective world where there are two persons: the vision of the situation for those who evaluate and those who are evaluated, the psycho-emotional aspect of the issue under consideration is also taken into account.ReferencesBallweg, S. Drumm, S. Hufeisen, B. Klippel, J., Pilypaityte, L. (2013). Wie lernt man die Fremdsprache Deutsch? Deutsch Lehren Lernen. Band 2. München: Klett-Langenscheidt.Beurteilen im DaF-/DaZ-Unterricht Testen – Evaluieren – Prüfen Akten der Vierten Gesamtschweizerischen Tagung für Deutschlehrerinnen und Deutschlehrer 29. und 30. Juni 2012 – Universität Bern. M. Clalüna, B. Tscharner (Eds.). Impressum Käser Druck.Bolton, S., Glaboniat, M., Lorenz, H., Perlmann-Balme, M., Steiner, S. (2008). Mündlich: Mündliche Produktion und Interaktion Deutsch: Illustration der Niveaustufen des Gemeinsamen europäischen Referenzrahmens. München: Langenscheidt.Garme, B. (2005). Auf den Flügeln der Sprache: Ein diagnostisches Verfahren. In: Anforderungen an Verfahren der regelmäßigen Sprachstandsfeststellung als Grundlage für die frühe und individuelle Förderung von Kindern mit und ohne Migrationshintergrund. (pp. 241-260), K. Ehlich u.a. (Eds.). Bonn: BMBF.Grotjahn, R. (2010). Sprachtests: Formen und Funktionen. In: Handbuch Fremdsprachendidaktik. (pp. 211–215). W. Hallet, F. Königs (Eds.). Seelze-Velber: Kallmeyer.Grotjahn, R., Kleppin, K. (2015) Prüfen, Testen, Evaluieren Klett-Langenscheidt München.Kleppin, K. (2010): Fehleranalyse und Fehlerkorrektur. In: Deutsch als Fremd- und Zweitsprache: ein Internationales Handbuch (1.Halbband). (pp. 1060-1072). H.-J. Krumm (Ed.). Berlin: Mouton de Gruyter.Krumm, H.-J. (2001): Bildungsstandards und Kompetenzorientierung – Herausforderungen für das Fach Deutsch als Fremdsprache. In: Theorie und Praxis. Österreichische Beiträge zu Deutsch als Fremdsprache. Bd. 14/2010. (pp. 171–185). H.-J. Krumm, P. R. PortmannTselikas, (Eds.). Innsbruck: Studienverlag.Lengyel, D. (2010). Language Diagnostics in multilingual settings with respect to continuous procedures as accompaniment of individualized learning and teaching. Strasbourg: Council of Europe. Retrieved from: http://www.coe.int/t/dg4/linguistic/Source/Source2010_Forum Geneva/1_Diagnostic Lengyel_EN.pdfRoche, J. (2010) Fremdevaluation und Selbstevaluation. In: Handbuch Fremdsprachendidaktik. (pp. 228–231). W. Hallet, F. G. Königs. (Eds.). Seelze-Velber: Kallmeyer.Rumpf, H. (1996). Wirklichkeiten berühren. Umrisse einer neuen Lernkultur. Fragen und Versuche, 77, 8–22.Shohamy, E. (2001). The Power of Tests: A Critical Perspective on the Uses of Language Tests. Harlow: Pearson Education.Smit, R. (2008). Formative Beurteilung im kompetenz- und standardorientierten Unterricht. Beiträge zur Lehrerbildung, 26(3), 383–392.Studer, T. (2010). Kompetenzmodelle und Bildungsstandards für Deutsch als Fremd- und Deutsch als Zweitsprache. In: Deutsch als Fremd- und Zweitsprache. Ein internationales Handbuch. (pp. 1264–1271). H-J. Krumm, C. Fandrych, B. Hufeisen, C. Riemer (Eds.). Berlin: De Gruyter. Bd. 2, Art. 142.Van Avermaet, P., Gysen, S. (2008): Language Learning, Teaching and Assessment and the Integration of Adult Immigrants. The Importance of Needs Analysis. Strasbourg: Council of Europe. Retrieved from: http://www.coe.int/t/dg4/linguistic/MigrantsSemin08_MainDocs_ EN.asp.